Teacher Strategies in Assessment of Fine Arts Learning in Early Childhood Education - Siti Khodijah Lubis; Adek Cerah Kurnia Azis; Ratno Susanto; Nur Qomariah Panjaitan; Siti Syawalina (Gorga : Jurnal Seni Rupa, 2025)
Assessment of fine arts learning in early childhood education (PAUD) plays a crucial role, whereby teachers focus not only on evaluating the products of children's work but also on the process itself. This study aims to describe the strategies employed by teachers in assessing fine arts learning in PAUD, encompassing both process-based and product-based approaches. The research method employed was library research, involving the review of relevant national and international articles published over the last five years. Data analysis was performed using thematic synthesis techniques. The results showed that process-based assessment strategies included direct observation, the use of the child development achievement checklist scale, and anecdotal notes. Meanwhile, product-based assessment strategies are carried out through children's work results and portfolios. Both forms of assessment provide a complete picture of children's development and form the basis for subsequent learning planning. This study concludes that fine arts assessment in early childhood education must emphasize a balance between process and product assessment to support children's holistic development and improve the quality of teachers' learning practices.